Unemployment Effects of Stay-at-Home Orders: Evidence from High-Frequency Claims Data - Baek, ChaeWon; McCrory, Peter B.; Messer, Todd; Mui, Preston (The Review of Economics and Statistics, 2021)
We use the high-frequency, decentralized implementation of stay-at-home (SAH) orders in the United States to disentangle the labor market effects of SAH orders from the general economic disruption wrought by the COVID-19 pandemic. We find that each week of SAH exposure increased a state's weekly initial unemployment insurance (UI) claims by 1.9% of its employment level relative to other states. A back-of-the-envelope calculation implies that of the 17 million UI claims between March 14 and April 4, only 4 million were attributable to SAH orders. We present a currency union model to provide conditions for mapping this estimate to aggregate employment losses.